História da Cartilha Progressiva (1907) nas escolas do Estado do Paraná - Collares, Solange Aparecida de Oliveira (2008)
This research has as regional cutting the State of Paraná, with the analysis of the progressive spelling book – the first spelling book of author paranaense, elaborated in 1900 and used up to 1907, whose method of reading teaching had been adopted officially in this State. This way it is believed that this research can contribute for the production in the area of the Historizes od the Brasilian Education. The term “spelling book” is the unfolding of the word “letter” that was used in Portuguese language from the beginning of the modern age for your time, to identify those texts printed, whose the explicit purpose would be it of teaching to read to write and to count the the word flowed of letter, therefore, as any didn´t exist text book until then, the teachers elaborated some hand written texts for the teaching of the reading, or they used letters, occupations and registry documents. Like this of the letters they happened to the spelling books. They were used initially in Brasil, the letters and later spelling books of Portuguese publisher, that for the first series, of the elementary schools. The spelling book found for analysis it was edicted in 1907, and used in schools paranaenses, it is called progressive schools. And it is of Lindolpho Pombo´s authorship – man that stood out as director of the public school and writer. To understand how the spelling books and your contribution appeared for the area of the education, it is necessary to understand some aspects of the history. The general objective of this research is to look for to understand in that social and political context appeared the progressive spelling book, the first of author paranaense, used in the State of Paraná for the public instruction, the specific objectives of this research: To analyse the first spelling book literacy paranaense, as well as your appearance and your importance; to investigate the pedagogic conception of the author explicited in the progressive spelling book; for us to reach the proposed objectives, Some documents were analysed originating from of the following places: Museum Paranaense; Public Library of Paraná; House of the Memory (Curitiba); Cycle of Studies of Bandeirantes; Public File of the State of Paraná; and other projects related to the research as the project Memory of the text book (USP/SP).